DNA Damage in Rheumatoid Arthritis: An Age-Dependent Increase in the Lipid Peroxidation-Derived DNA Adduct, Heptanone-Etheno-2′-Deoxycytidine - Ogawa, Masako (Hindawi Publishing Corporation, 2013)
Objective. To evaluate what types of DNA damages are detected in rheumatoid arthritis (RA). Methods. The DNA adducts such as 8-oxo-hydroxy-7,8-dihydro-2′-deoxyguanosine (8-oxo-dG), 1,N(6)-etheno-2′-deoxyadenosine (εdA), and heptanone-etheno-2′-deoxycytidine (HεdC) in genomic DNAs, derived from whole blood cells from 46 RA patients and 31 healthy controls, were analyzed by high-performance liquid chromatography tandem mass spectrometry, and their levels in RA patients and controls were compared. In addition, correlation between DNA adducts and clinical parameters of RA was analyzed. Results. Compared with controls, the levels of HεdC in RA were significantly higher (P < 0.0001) and age dependent (r = 0.43, P < 0.01), while there was no significant difference in 8-oxo-dG and εdA accumulation between RA patients and controls. HεdC levels correlated well with the number of swollen joints (r = 0.57, P < 0.0001) and weakly with the number of tender joints (r = 0.26, P = 0.08) of RA patients, while they did not show a significant association with serological markers such as C-reactive protein and matrix metalloproteinase 3. Conclusion. These findings indicate that HεdC may have some influence on the development of RA and/or its complications.